Utility of Computed Tomographic Enteroclysis/Enterography for the Assessment of Mucosal Healing in Crohn's Disease. (27th April 2013) - Hashimoto, Shinichi; Shimizu, Kensaku; Shibata, Hiroaki; Kanayama, Satoko; Tanabe, Ryo; Onoda, Hideko; Matsunaga, Naohumi; Sakaida, Isao
Abstract : Aim . When determining therapeutic strategy, it is important to diagnose small intestinal lesions in Crohn's disease (CD) precisely and to evaluate mucosal healing as well as clinical remission in CD. The purpose of this study was to compare findings from computed tomographic enteroclysis/enterography (CTE) with those from the mucosal surface and to determine whether the state of mucosal healing can be determined by CTE. Materials and Methods . Of the patients who underwent CTE for CD, 39 patients were examined whose mucosal findings could be confirmed by colonoscopy, capsule endoscopy, balloon endoscopy, or with the resected surgical specimens. Results . According to the CTE findings, patients were determined to be in the active CD group (n = 31 ) or inactive CD group (n = 8 ). The proportion of previous surgery, clinical remission, stenosis, and CDAI score all showed significant difference between groups. Mucosal findings showed an association with ulcer in 93.6% of active group patients but in only 12.5% of inactive group patients (P < 0.0001 ), whereas mucosal healing was found in 62.5% of inactive group patients but in only 3.2% of active group patients (P < 0.0001 ). Conclusion . CTE appeared to be a useful diagnostic method for assessment of mucosal healing in Crohn's disease.